2015
DOI: 10.1128/jcm.02483-14
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Epidemiology of Repeat Chlamydia trachomatis Detection after Treatment by Using C. trachomatis OmpA Genotyping

Abstract: Repeat Chlamydia trachomatis detection frequently occurs within months after C. trachomatis infection treatment. The origins of such infection (persistence versus reinfection from untreated or new partners) are varied and difficult to determine. C. trachomatis strains can be differentiated by sequencing the ompA gene encoding the outer membrane protein A (OmpA). We used OmpA genotyping to investigate the epidemiology of repeat C. trachomatis detection after treatment in C. trachomatis-infected subjects seen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…Sena et al reported 12 % RNA persistence after 4 weeks in men, while Dukers et al reported 42 % intermittent positive results up to 51 days [ 9 , 19 ]. In addition, a recent study reported 24 % positivity in 180 patients after 6 months, but no data on re-exposure or reinfections were reported [ 26 ]. Since none of these previous studies reported results from consecutive days, the exact time to clearance could not be determined, and prolonged persistence could not be distinguished from blips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sena et al reported 12 % RNA persistence after 4 weeks in men, while Dukers et al reported 42 % intermittent positive results up to 51 days [ 9 , 19 ]. In addition, a recent study reported 24 % positivity in 180 patients after 6 months, but no data on re-exposure or reinfections were reported [ 26 ]. Since none of these previous studies reported results from consecutive days, the exact time to clearance could not be determined, and prolonged persistence could not be distinguished from blips.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small sample size we could not identify characteristics associated with the occurrence of blips. However, the occurrence of blips, as well as reinfections, could explain the higher positivity rates reported by some studies, especially in those with very long follow-up and limited sampling [ 9 , 15 , 18 , 19 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants who tested negative for chlamydia at the first follow-up and who were still in a youth correctional facility on day 67 attended a second follow-up on that day for repeat nucleic acid amplification testing (to evaluate for persisting chlamydia that was not identified at the first follow-up) and for an interview in which the same information was collected as at the day 28 follow-up. Participants who tested positive for chlamydia at the first or second follow-up had OmpA genotyping performed on their urine specimens with the use of reported methods 21 to assess for concordant strains (identical ompA sequences); participants with suspected treatment failure had genotyping performed on urine specimens from both the enrollment visit and the follow-up visit.…”
Section: Methodsmentioning
confidence: 99%
“…Reagent kits (genomic DNA from tissue kits, Macherey-Nagel, Germany) were used to extract the DNA of C. trachomatis. DNA from the C. trachomatis endogenous plasmid was PCR-amplified using primers designed from those referenced in the literature (Kapil et al, 2015).…”
Section: Laboratory Testingmentioning
confidence: 99%